One Stop Service Public Innovation In The Non TPI Class I Immigration Office Serang City Indonesia - Kartika Shania Ningrum; Rethorika Berthanilla; Ahmad Sururi (Indonesian Journal of Social Science Research, 2020)
This study aims to determine the extent of implementation of the innovation one stop service at the Kantor Imigrasi Kelas I Non TPI Serang. This research uses descriptive method with qualitative approach. The technique of taking informants using snowball sampling technique combined with accidental sampling. This research was conducted at the Kantor Imigrasi Kelas I Serang from April 22, 2019 until August 27, 2019. The data were collected by observation, interview and documentation. Based on the results of this study concluded 1) innovation that run was good enough, 2) services provided when running the innovation was already good. While that is a contributing factor in the implementation of this innovation is 1) a queue at the immigration quota is not too much so as to sum up the work of immigration officers, 2) Immigration Office adequate facility for the community. Then the inhibiting factor is the lack of clear information dissemination to the public.